Social Relations Management On School Development - Moh. Nahrowi; Anik Nurmaidah (STAIFAS-Press, 2023)
Schools currently should be supported by society in order to develop relevant and adequate educational elements which start from human resources, curriculum tools, funding, management, good facilities, and infrastructure that are enough and able to accommodate schools’ needs. Social management needs to be designed in such a way as to invite the community to participate in developing schools and facilitating policy-making as the schools’ needs. Several strategies that can be implemented to reach communication in social relations management include community data collection, community mapping, community engagement, and community school involvement to develop education, funding, and consulting forms.